Meet the Expert : Unlocking AI with a Data Fabric with Sam Ramji and David Thomas - Ramji, Sam; Thomas, Dave (O'Reilly Media, Incorporated, 2020)
Today's companies face increasing complexity in their data management systems and in the policies that govern that data. Implementing a data fabric allows business groups to: Reduce their time to insights Operate with optimized data security Improve the usability of their data Remove the complexity affiliated with AI solutions Deloitte and their ecosystem partners are collaborating with leaders in enterprise data fabric to assist clients that are managing data sprawl and shadow data management with big data and AI projects. What you'll learn and how you can apply it By the end of this live show, you'll better understand: Create a smooth and secure flow of data for your AI workloads Enhance your data strategy to create workloads conducive to AI solutions Unify AI compute and data silos across sites and regions Scale your data platform to provide zero downtime, zero lock-in, and global scale Reimagine your organization through AI and robotic solutions by introducing data-powered innovation This event is for you because ... You want to learn about the fundamental shifts that are transforming the business landscape and customer needs You want to reduce time to insight, optimize data security, improve usability of your data, and remove the complexity affiliated with AI solutions Prerequisites: Come with your questions for Sam Ramji and David Thomas Have a pen and paper handy to capture notes, insights, and inspiration Recommended follow-up: Data Management at Scale The AI Ladder The AI Organization.